Los asientos de la Santa Hermandad con los concejos andaluces (1478) / The Entries of the Holy Brotherhood with the Andalusian Councils. - Collantes de Terán Sánchez, Antonio (Historia. Instituciones. Documentos, 2017)
RESUMEN: Este trabajo analiza los asientos establecidos entre los diputados generales de la Hermandad y varios concejos andaluces, por medio de los cuales se trató de poner fin a una serie de tensiones y conflictos que jalonó el primer año de vida de la institución en Andalucía. Dichos asientos, de los que se han conservado algunos y de otros han llegado referencias más o menos indirectas, fueron el resultado de una serie de negociaciones, iniciadas a partir de la Junta de Pinto-Madrid, en las que se acordaron tres cuestiones fundamentalmente: la liquidación de las deudas que los concejos venían arrastrando desde los primeros momentos de su integración, los recursos en hombres y dinero que debían poner a disposición de la Hermandad y la estructura orgánica local y provincial. ABSTRACT: This paper analyses the entries between the Brotherhood’s general deputies and several Andalusian councils, through which it was tried to end a series of tensions and conflicts that marked out the first months of the life of the institution in Andalusia. These entries, some of which have been preserved and we have more or less indirect references from some others, were the result of a series of negotiations, promoted from the Junta of Pinto-Madrid, in which it was basically agreed three matters: the settlement of the debts that the councils were dogging since the first moments of their creation, the economical and human resources they should put at the Brotherhood’s disposal and the local and county organical structure.